Methods of Cancer Diagnosis, Therapy and Prognosis Colorectal Cancer - Hayat, M. A. (Methods of Cancer Diagnosis, Therapy and Prognosis, 2009)
This fourth volume in the series Methods of Cancer Diagnosis, Therapy and Prognosis discusses various methodologies for the diagnosis, therapy and prognosis of Colorectal Cancer. Both standard and emerging therapies for this cancer, written by expert oncologists/pathologists in this field, are included. This fully illustrated volume: * Presents surgical, radiological, and molecular therapies and prognostic markers for colorectal cancer. * Highlights a large number of methods for diagnosing colorectal cancer at various stages of development, including immunohistochemistry, in situ hybridization immunoscintigraphy, RT- PCR, free circulating DNA levels in blood and stool, ultrasonography, CT, PET, and MRI. * Includes imaging technologies for assessing treatment results, and details related to colonoscopy and sigmoidoscopy. * Explains the use of anticancer agents and monoclonal antibodies, including 5-fluorouracil, fluoropyrimidines, leucovorin, irinotecan, oxaliplatin, raltitrexed, capecitabine, cetuximab, and bevacizumab. * Compares preoperative chemoradiotherapy with postoperative chemoradiotherpy. The technological advances presented in this volume are expected to expedite new discoveries and their translation to clinical practice. The field of oncology will benefit the most from these advanced methods, as a combination of therapies and personalized medicine will improve early detection of colorectal cancer and other cancer types. Professor Hayat has summarized the problems associated with the complexities of research publications and has been successful in editing a must-read volume for oncologists, cancer researchers, medical teachers and students of cancer biology.